الأشتر النخعيّ (حياته وشعره) - أحمد, عدنان (Latakia University Journal - Arts and Humanities Sciences Series, 2018)
يهدف هذا البحث إلى التعريف بواحد من الشعراء المقلين الذين عاشوا في صدر الإسلام، هو مالك بن الحارث النخعي المعروف بـ "الأشتر"، الذي كان من أبرز أنصار الإمام علي بن أبي طالب كرم الله وجهه، ومن أشدهم على خصومه، وله في ذلك مواقف كثيرة مشهورة مذكورة في كتب التاريخ والأدب. والبحث يقسم إلى قسمين، أما القسم الأول فكان للحديث عن الشاعر، عن نسبه، وصفاته، وإسلامه، وحياته، بما تتضمنه تلك الحياة من مواقف وأحداث مهمة، ثم ينتهي هذا القسم بالحديث عن وفاته. أما القسم الثاني فقد خصص للشعر، إذ قمنا بجمع شعر الشاعر من مظانه، ثم جعلنا الشعر أولاً ثم الرجز. وكنا قبل ذلك قد تحدثنا عن قلة شعره وحاولنا أن نشير إلى أبرز أسبابها. This piece of research aims at identifying one of, poetically speaking, non-lucrative poets who lived in the beginning of the Islamic Era: Malek Ibn Al-Hareth known as "Al-Ashter". He was one of the staunchest supporters of Ali Ibn Abi Taleb (God bless him), and one of the hardest fighters against his opponents. Such instances about his numerous and popular attitudes are extremely obvious in books of history and literature. This piece of research is divided into two sections. The first section speaks about the poet, his ancestry, his personal characteristics, his belief in Islam, and his life including all those significant events and stances that characterize it. This section concludes with highlighting his death. The second section is devoted to his poetry. I have collected his poetical production from its various sources. Poetry has been the first subject matter, as I have found it so important to start with, and followed up and ended with rajz (a special kind of rhymed verse). This is irrespective of the fact that I have demonstrated his rare poetical production, and at the same time, illustrating the reasons lagging behind this literary phenomenon.